National Survey of Investigations in the Community Policing Context, 1997 - Wycoff, Mary Ann ([Verlag nicht ermittelbar], 2001)
This survey collected descriptive information from municipal police departments and sheriffs offices across the United States to determine whether the departments had implemented community policing, how their investigative functions were organized, and the ways in which their investigative organizational structure may have been modified to accommodate a community policing approach. The research project involved a national mail survey of municipal police departments and sheriffs offices in all jurisdictions with populations of more than 50,000 and 100 or more sworn officers. The survey was mailed in the late fall of 1997. Data contain responses from 405 municipal departments and 196 sheriffs offices. Questionnaires were similar but were modified depending on whether they were sent to municipal or sheriffs agencies. Data generated by the questionnaires provide descriptive information about the agencies, including agency type, state, size of population served, number of full-time and part-time sworn and civilian personnel, number of auxiliary and rescue personnel, number of detectives, whether the sworn personnel were represented by a bargaining unit, and if the agency was accredited. Respondents reported whether community policing had been implemented and, if so, identified various features that described community policing as it was structured in their agency, including year implementation began, number of sworn personnel with assignments that included community policing activities, and if someone was specifically responsible for overseeing community policing activities or implementation. Also elicited was information about the organization of the investigative function, including number of sworn personnel assigned specifically to the investigative/detective function, the organizational structure of this function, location and assignment of investigators or the investigative function, specialization of detectives/investigators, their pay scale compared to patrol officers, their relationship with patrol officers, and their chain-of-command. Finally, respondents reported whether the investigative structure or function had been modified to accommodate a community policing approach, and if so, the year the changes were first implemented.